Surgical Management of Multijoint Septic Arthritis due to Rat-Bite Fever in a Pediatric Patient: A Case Study. (31st January 2017) - Wegner, Adam M.; Look, Nicole; Haus, Brian M.
Abstract : In the United States, rat-bite fever is a rare systemic illness principally caused by Streptobacillus moniliformis, an organism found in the nasopharyngeal flora of rodents. Infection through direct exposure to rat excreta such as saliva, urine, or feces can lead to fever, rash, and an asymmetric migratory polyarthritis. As rodents are becoming more popular as pets, more pediatric cases are being documented. We report a pediatric case of delayed onset septic arthritis in the left wrist and right knee due to S. moniliformis from a rat bite. Previously reported pediatric case studies of suppurative arthritis due to S. moniliformis have only involved the hip. This case study demonstrates the importance of a thorough exposure history and consideration of zoonotic infections as a cause of septic arthritis in a pediatric patient that requires antibiotics and surgical intervention.